2019
DOI: 10.20411/pai.v4i1.304
|View full text |Cite
|
Sign up to set email alerts
|

Sex Differences in the Association of Fat and Inflammation Among People with Treated HIV Infection

Abstract: Introduction: Ectopic fat deposition may contribute to chronic inflammation in people with HIV (PWH). To inform future mechanistic studies of metabolic risk in this population, we sought to determine which fat measures relate more strongly to inflammation and whether the fat-inflammation relationship is modified by sex or HIV status.Methods: We conducted a cross-sectional study of 105 PWH and 20 age- and sex-matched HIV-negative controls. Interleukin-6 (IL-6) and high-sensitivity C reactive protein (hs-CRP) le… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 31 publications
0
7
0
Order By: Relevance
“…Meanwhile, EAT is associated with CVD risk in HIV patients, independent of traditional CVD risk factors [ 44 ]. The clinicians could measure EAT to identify the phenotype of adiposopathy (i.e., “sick fat”) among treated patients with HIV infection; then, targeting these patients with lifestyle interventions and metabolic therapies may reduce the levels of chronic inflammation and immune activation that are thought to contribute to a wide range of HIV chronic comorbidities such as CVD [ 30 ].…”
Section: Discussionmentioning
confidence: 99%
“…Meanwhile, EAT is associated with CVD risk in HIV patients, independent of traditional CVD risk factors [ 44 ]. The clinicians could measure EAT to identify the phenotype of adiposopathy (i.e., “sick fat”) among treated patients with HIV infection; then, targeting these patients with lifestyle interventions and metabolic therapies may reduce the levels of chronic inflammation and immune activation that are thought to contribute to a wide range of HIV chronic comorbidities such as CVD [ 30 ].…”
Section: Discussionmentioning
confidence: 99%
“…Women vs men may be at heightened risk of inflammatory consequences associated with metabolically unhealthy fat including HIV-related adipocyte hypertrophy [ 76 , 77 ] and ectopic fat accumulation [ 78 , 79 ]. A cross-sectional study of PWH and age-/sex-matched HIV-negative persons found that HIV did not significantly modify the association of chronic inflammatory markers and ectopic adipose tissue; however, there was a statistically significant sex difference in correlations between interleukin 6 (IL-6) and BMI [ 80 ] ( Table 4 ).…”
Section: Metabolic Dysfunctionmentioning
confidence: 99%
“…Increased EAT volume, is associated with HIV infection, ART duration, and subclinical coronary atherosclerosis. Specifically, cardiac ectopic fat burden in PLWH appears to be correlated with HIV infection and ART, independently of traditional risk factors [28‐32,37]. A clear association between EAT volume and CD4 T‐cell count was first reported in two studies conducted by Guaraldi et al and Zona et al [28,29].…”
Section: Epicardial/pericardial Adipose Tissue (Table 2)mentioning
confidence: 99%
“…Inflammation and immune markers were significantly related to PAT volume and/or density, while their changes over 96 weeks were weakly but positively associated with PAT volume/density. Subsequently, the same group found that left atrium roof density was more strongly associated with systemic inflammation than peri‐right coronary artery fat in PLWH, highlighting that there may be regional vascularity differences in the association of PAT with the adiposopathy phenotype [37]. Interestingly, the fat‐inflammation relationship was stronger for women than for men, but did not differ by HIV status, indicating that future clinical studies of metabolic risk and inflammation among PLWH should include sex‐stratified analyses.…”
Section: Epicardial/pericardial Adipose Tissue (Table 2)mentioning
confidence: 99%